Sistem Informasi Geografis Pemetaan Salon Untuk Rekomendasi Di Provinsi Aceh Menggunakan Metode Simple Additive Weighting - Safwandi, Safwandi; Safira, Mela; Razi, Ar (Jurnal Inovatif, 2024)
Salon service providers are companies that provide hair, facial, body and other beauty treatments to the public. Many people are currently doing business in this field, and many business people are opening salons in various locations, starting from city areas and densely populated village areas. In Aceh Province there are 200 salons. The benefit of this application is that it can identify the recommended salons for each city/district and the shortest route to the salon that the service user will go to. In the initial stage, spatial data on salons in Aceh Province was collected and entered into a geographic database. The weights of relevant criteria such as service quality, price, location, sanitation cleanliness, and customer service are determined using the SAW method. After that, SAW is used to calculate the total score for each salon based on these criteria. Salons are then ranked by highest total score to provide recommendations that match user preferences. Next, Dijkstra's algorithm is used to determine the shortest route between the user's location and the selected salon. This helps users to plan trips efficiently and save time. The implementation of GIS and algorithms is integrated in the form of a website to facilitate access and use by the general public. Users can easily find the best salon based on their selection criteria, as well as get optimal directions. It is hoped that this research can contribute to advancing the salon industry in Aceh Province by providing practical and effective solutions for the public in choosing a salon that suits the community's needs.